Nuclear knowledge management system in the Republic of Belarus - Sytova, Svetlana N. (Journal of the Belarusian State University. Physics, 2022)
The article provides an overview of the basic concepts in the field of knowledge management, taking into account the recommendations of the United Nations in this area, as well as the nuclear knowledge management from the perspective of the International Atomic Energy Agency. The assessment of the state of nuclear knowledge management in the world, Eurasian Economic Union countries and Republic of Belarus has been carried out. The information and analytical activities and the specifics of the work of the national regulator in the field of nuclear and radiation safety – Department of Nuclear and Radiation Safety of the Ministry for Emergency Situations of the Republic of Belarus (Gosatomnadzor) – in the field of nuclear knowledge management were analysed, as well as the best practices in this area in the Republic of Belarus. A description of modern information technologies for nuclear knowledge management system is given, including the further development of the capabilities and tools of software products – Intellectual information system of an employee of Gosatomnadzor to ensure control (supervision) in the field of nuclear and radiation safety and electronic portal of nuclear knowledge of the Republic of Belarus BelNET (https://belnet.bsu.by/ ). The basic principles for work and further development of nuclear knowledge management system in the Republic of Belarus are presented.